Low reported taste function is associated with low preference for high protein products in advanced oesophagogastric cancer patients undergoing palliative chemotherapy. Issue 1 (February 2019) - de Vries, Y.C.; Boesveldt, S.; Kampman, E.; de Graaf, C.; Winkels, R.M.; van Laarhoven, H.W.M.
Summary: Background & aims: Cancer patients undergoing palliative chemotherapy can experience a variety of chemosensory and food preference changes which may impact their nutritional status and quality of life. However, evidence of these changes in oesophagogastric cancer (OGC) patients is currently mostly qualitative and not supported by quantitative data. The aim of this study was to assess how self-reported and objective taste and smell function and food preferences change over time during chemotherapy in OGC patients. Methods: This observational study included 15 advanced OGC patients planned for first line treatment with capecitabine and oxaliplatin. Participants completed two test sessions scheduled before start of cytotoxic treatment and after two cycles. Self-reported and objective taste and smell function and the macronutrient and taste preference ranking task were conducted at each test session. Results: Self-reported taste and smell did not change upon chemotherapy. Objective taste function decreased during chemotherapy, although this was not statistically significant (p = 0.06), objective smell function did not change. Before and during chemotherapy, high protein foods were preferred over high carbohydrate and over low energy products, but food preferences did not change over time. A lower self-reported taste function correlated with a lower preference for high-protein products (ρ = 0.526, p = 0.003). Conclusion: This study suggests that objective taste function decreases during chemotherapy in OGC patients, but not smell function. A low reported taste function was related to a lower preference for high-protein products.